A formação para a educação inclusiva nos projetos pedagógicos curriculares dos cursos de licenciatura da UFES/Alegre - ES - Cossate, Fernanda Sobreira (2019)
As a rule, the process of exclusion in school practice was a reality that after the declaration of human rights in 1948 became questionable and repudiated. Throughout this historic milestone, several agreements were signed, to which Brazil is a signatory, among them the Salamanca declaration. These agreements aimed to provide north that could guide the formation of the inclusive education paradigm in the different countries of the world. Many authors have sought to study and understand the differences and describe how the process of exclusion occurs from those who, because they are different, suffer the epistemicide of their ideas and knowledge in the face of the knowledge of those who have economic and social power in a society, in which diversity must be launched beyond visibility. In invisibility lies everything that represents the different in a society deeply marked by the search for cultural homogeneity to the detriment of other epistemologies. In this context arise authors of critical and post-critical theoretical approaches to the idea of school curriculum, whose theoretical frameworks are Paulo Freire, Giroux and Laclau, respectively and work the idea of emancipation, important in the process of changes of the political and social system and especially In the context of education, they profoundly influence the constitution of a curriculum capable of embracing the various social demands represented by human diversity. In this context, this paper is a case study of the four undergraduate courses of the Federal University of Espírito Santo, Unit of Alegre- ES and aims to analyze how the curricular structure of the undergraduate courses contribute to teacher education from the perspective of inclusive education.To this end, a documental analysis of the pedagogical political projects of these courses was carried out and their adaptation to the national curriculum guidelines that guide each degree. In addition, two focus groups were held with faculty members of the Structuring Teacher Nucleus (NDE) of each. of the courses to identify which political and pedagogical aspects have been influencing the teachers formation regarding the aspects of the inclusive education. The data from this research indicate that there is the adequacy of the PPC's analyzed to the national curriculum guidelines that guide the undergraduate courses studied, as well as the strong technical aspect of the courses which corroborates the historical data regarding teacher education in Brazil, which It still has a focus on bachelor degree to the detriment of undergraduate degrees, which at first becomes an aggravating factor of teacher education focused on inclusive education. At the same time, when the legislation of the courses is adequate, regarding the infrastructure, pedagogical support to the coordinators and teachers and the political articulation between Municipal Public Administration and Federal University still need improvement. However, the potential of highly qualified faculty courses constitutes a great opportunity for the development of the theme.